Sustainable hospitality management : designing meaningful encounters with talent and technology - Ruël, Huub; Lombarts, Angelique (Emerald Publishing Limited, 2020)
Sustainable Hospitality Management: Designing Meaningful Encounters with Talent and Technology will generate international debate in the research and practice of hospitality management. It considers how the sector can and should innovate to respond to challenges such as talent scarcity, the growing ecological footprint, and technological developments. Volume 24 of Advanced Series in Management explores topics at the very heart of hospitality, by looking at meaningful encounters: positive, welcoming, genuinely service-oriented interactions between humans, and the role of technology in creating or improving these encounters. Human talent is essential to excellent service delivery and guest experience provision. It is also essential in the design and monitoring of technology-enabled guest or customer experience. Technology may be the service facilitator or it may be an experience enhancer. In today's globalizing platform economy, hospitality services are established most dominantly via technology-enabled platforms or networks. At the human interaction level, technology can deliver, support or intensify the hospitality experience. This volume is essential for researchers and students interested in the hospitality sector and the role of technology in creating a sustainable hospitality sector.
Includes index.
Keywords: Hospitality industry -- Management.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality industry.; elektronické knihy; electronic books